Serum neurofilament light chain as a reliable biomarker of hereditary transthyretin‐related amyloidosis—A Swiss reference center experience - Loser, Valentin; Benkert, Pascal; Vicino, Alex; Lim Dubois Ferriere, Pansy; Kuntzer, Thierry; Pasquier, Jérôme; Maceski, Aleksandra; Kuhle, Jens; Theaudin, Marie (Journal of the peripheral nervous system, 2023)
Hereditary transthyretin‐related (hATTR) amyloidosis is a rare disease, causing a disabling and life‐threatening axonal length‐dependent polyneuropathy. Monitoring of disease progression and treatment response is difficult. We aimed to determine if serum neurofilament light chain (sNfL) is a reliable and early biomarker of peripheral neuropathy in hATTR amyloidosis. We prospectively included 20 hATTR patients, 14 symptomatic and 6 asymptomatic. Patients were assessed at baseline and 1 year, including a full clinical examination with disease severity and functional scores, electrochemical skin conductance measurement with Sudoscan and nerve conduction studies, and sNfL level. hATTR patient sNfL were also compared with sNfL of 4532 healthy controls of a reference database by calculating age and BMI‐adjusted Z scores. At baseline, median sNfL concentration was 3.6‐fold higher in symptomatic than asymptomatic hATTR patients (P = .003), and this difference was also found in our under 60‐years‐old patients (P = .003). There was no significant difference of sNfL concentration between asymptomatic patients and healthy controls (Z‐score of −0.29), but a significant difference between symptomatic patients and healthy controls (Z‐score of 2.52). We found a significant correlation between sNfL levels and most clinical and electrophysiological disease severity scores, the strongest correlation being with the NIS score. sNfL seems to be a reliable biomarker of peripheral neuropathy severity in hATTR amyloidosis and can distinguish between asymptomatic and symptomatic patients. sNfL could also become a reliable biomarker to establish disease onset and treatment response.